Copolymers of 3-arylthieno[3, 2-b]thiophenes bearing different substituents: Synthesis, electronic, optical, sensor and memory properties. (5th May 2022) - Gunturkun, Dilara; Isci, Recep; Sütay, Berkay; Majewski, Leszek A.; Faraji, Sheida; Ozturk, Turan
Graphical abstract: Highlights: Easy synthesis of TT based polymers containing various functional groups. Mega Stokes shift of 138 nm. High fluoride anion sensing feature for both absorption and emission. Memory devices with perfect performance of 10 6 ON/OFF ratio. Good retention time and stable stress constant data storage. Abstract: Thienothiophene (TT) is one of the most impressive organic cores, and has gained significant attention in the organic polymeric materials in recent years. Possessing cyano (CN), carboxylic acid (COOH) and dimethylamine (N(CH3 )2 ) substituted thieno[3, 4- b ]thiophene (TT), π-extended conjugated three novel polymers (P1-P3 ) with 3-hexylthiophene were successfully synthesized by the Suzuki coupling. All the polymers were found to be well soluble owing to the side chains. Their optical and electrochemical properties were investigated by experimental and computational studies. Moreover, the photophysical characterization of the novel polymers demonstrated a significant mega Stokes shift, reaching 138 nm with a bathochromic shift, and a changing electronic band gap between 1.91 and 2.33 eV as well as good thermal stability of degradation temperature around 320 °C. Also, their F − anion-recognition abilities have been investigated with selectivity of different fluoride concentration for UV and emission titration spectra. Memristive switching properties were examined by using synthesized polymers as an active layer in memory devices. The highest ON/OFF ratio of the memory devices were recorded to be 10 6 with good stability, which makes them suitable for electronic applications.